Retrospective observational study of the use of artemether-lumefantrine in the treatment of malaria in Japan. Issue 22 (March 2018) - Nakamura-Uchiyama, Fukumi; Katanami, Yuichi; Kikuchi, Tadashi; Takaya, Saho; Kutsuna, Satoshi; Kobayashi, Taiichiro; Mizuno, Yasutaka; Hasegawa, Tetsuo; Koga, Michiko; Yoshimura, Yukihiro; Hasegawa, Chihiro; Kato, Yasuyuki; et al.
Abstract: Background: The Research Group on Chemotherapy of Tropical Diseases, Japan, introduced artemether–lumefantrine (AL) in late 2002, mainly for treating uncomplicated Plasmodium falciparum malaria. Because AL was on the market in Japan in March 2017, the effectiveness and safety of AL were analyzed to help medical personnel use AL optimally. Methods: Case report forms submitted by the attending physicians were analyzed. When necessary, direct contact with the attending physicians was made to obtain detailed information. Results: Effectiveness analysis was performed for 62 cases and safety analysis was performed for 66 cases. In P. falciparum malaria, the overall cure rate was 91.1% (51/56), of which the cure rates for Japanese and non-Japanese patients were 82.1% (23/28) and 100% (28/28), respectively. The successfully treated cases included severe P. falciparum malaria, with parasite densities exceeding 500, 000/μL. Adverse events were reported in 14 patients, including delayed hemolytic anemia which occurred in the top four highest parasitemic cases. Conclusions: AL treatment failure in P. falciparum malaria may not be rare among non-immune individuals, including Japanese. The possibility of delayed hemolytic anemia, which occurs preferentially in high parasitemic cases, should be considered following AL treatment.